2021
DOI: 10.2147/cmar.s302423
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-4-Hydroxylase α Subunit 2 as a Novel Potential Biomarker for Predicting the Prognosis of Epithelial Ovarian Carcinoma

Abstract: Objective Epithelial ovarian cancer (EOC) is one of the leading causes of death worldwide. The aim of this study was to explore the prognostic significance of prolyl-4-hydroxylase α subunit 2 (P4HA2) in patients with EOC. Patients and Methods A total of 217 clinical samples (EOC tissues, 167 cases; normal ovarian, 50 cases) were collected and pathologically confirmed using hematoxylin and eosin (H&E) staining. P4HA2 expression in clinical samples was stained by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Collagen is an essential component of the extracellular matrix [43], which can promote tumor development by initiating tumor cell proliferation, invasion, migration, epithelial-mesenchymal transition, and chemoresistance [44][45][46]. Abnormal P4HA2 expression indicates a poor outcome in liver, cervical, and ovarian cancers [47][48][49]. Aspirin represses P4HA2 expression through NF-κB and LMCD1-AS1/let-7 g pathways, inhibiting collagen deposition and preventing HCC progression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is an essential component of the extracellular matrix [43], which can promote tumor development by initiating tumor cell proliferation, invasion, migration, epithelial-mesenchymal transition, and chemoresistance [44][45][46]. Abnormal P4HA2 expression indicates a poor outcome in liver, cervical, and ovarian cancers [47][48][49]. Aspirin represses P4HA2 expression through NF-κB and LMCD1-AS1/let-7 g pathways, inhibiting collagen deposition and preventing HCC progression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, collagen is an important component of the extracellular matrix (ECM)(Gorres and Raines 2010), which can ultimately promote tumor development by promoting tumor cell proliferation, invasion, migration, epithelial-mesenchymal transition (EMT), and chemoresistance (Yang et al 2014;Zheng et al 2017;Yamazaki et al 2018). Recently, abnormal expression of P4HA2 has been continuously reported as a marker of poor disease prognosis in tumors such as liver cancer, cervical cancer, and ovarian cancer (Cao et al 2020;Zhang and Zhao 2021;Shang et al 2022). Simultaneously, it has also been shown that aspirin reduces the expression level of P4HA2 through the NF-κB and LMCD1-AS1/let-7g pathways, thereby inhibiting collagen deposition and preventing the progression of hepatocellular carcinoma (Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The prolyl 4‐hydroxylase subunit alpha 2 ( P4HA2 ) gene encodes a component of prolyl 4‐hydroxylase, a key enzyme in collagen synthesis 9 . Several studies have reported that P4HA2 is highly expressed in many cancers and participates in cancer progression 10–14 . These studies are often associated with collagen expression in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have reported that P4HA2 is highly expressed in many cancers and participates in cancer progression. [10][11][12][13][14] These studies are often associated with collagen expression in cancers. Collagen is the main structural protein component of the extracellular matrix (ECM), 15 and the biochemical and biophysical properties of ECM are essential for the survival, growth, invasion, and drug resistance of tumor cells.…”
Section: Introductionmentioning
confidence: 99%